An online routing algorithm for space division multiplexing-based elastic optical networks. (21st January 2020) - Iyer, Sridhar
We focus on the optimisation of lightpath routing in an online space division multiplexing-based elastic optical network (SDM-b-EON). We propose a new online routing algorithm, named as online routing algorithm (ORA), which accounts for the presence of the transceivers in the network, and also ensures the routing of the transparent lightpaths through the spectral super-channels over spatial multiple core fibres (MCFs) links. We conduct extensive simulations considering two realistic network topologies and two different MCF crosstalk values which result in different transmission reach values. The obtained results demonstrate that: 1) ORA significantly outperforms the various reference routing techniques in terms of the bandwidth blocking probability (BwBP); 2) in regard to the use of modulation formats, for low crosstalk values, the most used format is QPSK rather than BPSK which results in lesser traffic being accepted by the SDM-b-EON; 3) as the transceivers amount increases, more frequent demands blocking occurs owing to spectrum scarcity. Overall, our study shows that in a SDM-b-EON, larger amount of transceivers can be efficiently used in comparison to the less efficient spectrum usage, since the spectrum significantly experiences fragmentation owing to the spectrum-contiguity and spectrum-continuity constraints.